2017
DOI: 10.1111/ijcs.12385
|View full text |Cite
|
Sign up to set email alerts
|

Debunking the myth of general consumer rejection of green genetic engineering: Empirical evidence from Germany

Abstract: The emergence of a more sustainable economy in Europe was accompanied by a range of biobased products and technologies. As a prominent example, green genetic engineering opens up multiple options to increase agricultural production, but its public acceptance seems to vary by application area. Risk perception explains consumer acceptance of green genetic engineering, which is a necessary precondition for wider technology adoption. This study investigates risk perceptions for four major sources of risk: health r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In addition to regional heterogeneity, Hess et al (2016) identify average income, food product characteristics, the characteristics of the biotechnology, knowledge and the information provided in the survey as explanatory factors for GM attitudes. Recently, Butkowski et al (2017) conducted a laboratory experiment in Germany, investigating the risk perceptions of different types of genetic engineering. They find that the level of perceived risk is significantly higher for food than bioenergy, which is mostly driven by higher perceived health risks.…”
Section: Literaturementioning
confidence: 99%
“…In addition to regional heterogeneity, Hess et al (2016) identify average income, food product characteristics, the characteristics of the biotechnology, knowledge and the information provided in the survey as explanatory factors for GM attitudes. Recently, Butkowski et al (2017) conducted a laboratory experiment in Germany, investigating the risk perceptions of different types of genetic engineering. They find that the level of perceived risk is significantly higher for food than bioenergy, which is mostly driven by higher perceived health risks.…”
Section: Literaturementioning
confidence: 99%
“…In specific, Hudson et al (2015) have illustrated the large importance that perceptions of the environmental impact of this technology have in orienting consumer approval towards GM food in EU member states, something also confirmed in country-specific EU studies. For example, Butkowski et al (2017) found that consumer perceptions of the environmental risk of GM food were the highest amongst the four different dimensions considered, while Grunert et al (2003) suggested that greater perceptions of environmental risks fostered more negative attitudes towards GM food amongst European consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to seed production and breeding are limited to the perceived risks and benefits of genetic engineering (e.g. Butkowski et al., 2017; Christoph et al., 2008; Delwaide et al., 2015; Emberger‐Klein et al., 2016; Nielsen, 2013; Wuepper et al., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%